Nutrient Intake, Nutrition Status and Hemoglobin Concentration of Lacto-ovo-vegetarians and Non-vegetarians - . Herman; Emma S Wirakusumah; Nino Yayah Sadiyyah (Media Gizi dan Keluarga, 2000)
In order to give more information about food intake level, nutrition status and hemoglobin concentration of lacto-ovo-vegetarians and in turn increasing human life quality especially vegetarians, a study was conducted in vihara Duta Mas Maitreya Jakarta with 30 samples of lacto-ovo-vegetarians and 30 samples of non-vegetarians.Energy and protein intake is not significantly different between non-vegetarians and lacto-ovo-vegetarians. But apparently there is a tendency that energy and protein intake of non-vegetarians (1826 kcal and 51.16 g) are higher than of lacto-ovo-vegetarians (1810 kcal and 42.54 g). On the contrary Fe and vitamin C of non-vegetarian (12.63 mg and 81.00 mg) are lower than lacto-ovo-vegetarians (12.84 mg and 139.93 mg). Statistically vitamin C consumption level are different between groups of respondents (p